Overexpression of the apple expansin-like gene MdEXLB1 accelerates the softening of fruit texture in tomato - Yan-hui CHEN; Bin XIE; Xiu-hong AN; Ren-peng MA; De-ying ZHAO; Cun-gang CHENG; En-mao LI; Jiang-tao ZHOU; Guo-dong KANG; Yan-zhen ZHANG (Journal of Integrative Agriculture)
Fruit firmness is an important quality trait of apple fruit texture, and the pre-harvest ripening period is the key period for the formation of apple fruit texture. Expansin is a cell wall loosing protein family that has four subfamilies: α-expansin (EXPA), β-expansin (EXPB), expansin-like A (EXLA), and expansin-like B (EXLB). In this study, we investigated the key period of pre-harvest texture formation in ‘Golden Delicious’ apples based on fruit longitudinal diameter, transverse diameter, firmness, tissue structure, respiration intensity, ethylene release rate, and expansin activity. Within the 10 days before harvest, the fruit was found to reach maturity. Semi-quantitative RT-PCR revealed that most of the expansins were expressed at the ripening stage before harvest. The biological function of the EXLB subfamily gene, MdEXLB1, was further identified, and its subcellular localization on the cell wall was confirmed by transient transformation experiments. Compared with the wild type (WT), the transgenic tomato lines overexpressing MdEXLB1 had lower plant height, earlier fruiting period, fewer days for fruit ripening, higher fruit maturity, lower fruit firmness, higher fruit expansin activity, more discrete flesh cell structure, and accelerated fruit ripening process. Overall, this is the first study to propose that the apple EXLB subfamily gene, MdEXLB1, has biological functions and plays an important role in promoting fruit ripening and softening.